Peer Group Support on Self-Efficacy, Glicemic Control and Self Care Activities in Diabetes Mellitus Patients - Ilkafah Ilkafah; Kusnanto Kusnanto (Jurnal Ners, 2014)
Introduction: Diabetes mellitus (DM) is a chronic disease with many complications. Self-efficacy is a psychosocial aspects refer to patient’s belief about their ability to do Diabetes managements. Self-efficacy can be enhanced by providing a mutual support from other Diabetic patients. This study aimed to analyze the influence of peer group support on self-efficacy, glicemic control and self-care activities of Diabetic patients.Method: This research was a pre-experimental with one-group pre-post test design and was evolved 29 respondents. Peer Group Support indicators were checking in, presenting problems, clarifying issues, sharing experiences, action planning and checking out. Implementation of peer group support activity was 60 minutes meeting, once a week for totally 6 weeks. The datas were analyzed by Wilcoxon signed rank test and Spearman’s Rho test with significance values p≤ 0.05.Result: Self efficacy, self care activities, and blood glucose level were increased (p=0.000).Discussion: Peer group support was recommended to enhance self-efficacy and self-management of diabetic patients. Further research is needed about health promotion for improving self-efficacy.